Risk Factors and Consequences of Cage Subsidence after Single-level Posterior or Transforaminal Lumbar Interbody Fusion: A Retrospective Multicenter Study - Hoai T.P. Dinh; Hiroki Ushirozako; Tomohiko Hasegawa; Shigeto Ebata; Tetsuro Ohba; Hiroki Oba; Keijiro Mukaiyama; Yu Yamato; Go Yoshida; Tomohiro Banno; Hideyuki Arima; Shin Oe; et al. (Spine Surgery and Related Research)
Introduction: Cage subsidence (CS) after posterior or transforaminal lumbar interbody fusion (PLIF or TLIF) is challenging; however, its impact on health-related quality of life (HRQOL) remains unclear. This study aimed to explore the impact of CS occurrence on HRQOL and identify the risk factors in patients following PLIF or TLIF. Methods: A total of 138 patients (mean age, 67 years; follow-up period, 12 months) who underwent single-level PLIF or TLIF were retrospectively analyzed. CS was defined as >1 mm sinking of the intervertebral cage evaluated via computed tomography. The patients were divided into the CS and nonsubsidence (NS) groups. HRQOL was assessed using the Oswestry Disability Index (ODI) scores. Results: Among the 138 patients, 30 (22%) developed CS following PLIF or TLIF. All cases with TLIF surgery (n=25) involved the use of one cage. A significant difference was observed in the use of two cages between the CS and NS groups (20.0% vs. 48.1%; P=0.006). The CS group had lower occupancy rate of autograft soon after the operation than the NS groups (P=0.002), and the occupancy rate of autograft tended to decrease in the CS group compared with the NS group over time. The ODI scores improved in both groups postoperatively; however, the NS group exhibited greater improvements in ODI scores from 4 months postoperatively. The CS group had a significantly lower proportion of patients with intervertebral osseous union at 6 and 12 months postoperatively compared with the NS group (P=0.003 and P<0.001, respectively). Conclusions: The use of two intervertebral cages may enhance initial stability and reduce CS risk after PLIF. Initial intervertebral stability was crucial to preventing CS occurrence, as evidenced by the high occupancy rates of autograft in patients without CS. Surgical factors, including surgical strategy and intraoperative techniques, should be considered to prevent CS occurrence and to improve surgical outcomes and patient satisfaction.